Overtourism in a City Destination from the Perspective of Entrepreneurs: Evidence from Wroclaw, Poland - FEDYK, Wojciech; SOŁTYSIK, Mariusz; RÓLCZYŃSKI, Tomasz; TAHERI, Babak; BORZYSZKOWSKI, Jacek; OKUMUS, Fevzi (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.14.2(66).14, 2023)
This study investigates how overtourism, as perceived by entrepreneurs operating in the local tourism economy, manifests itself in a large city – Wroclaw (Poland). Data were collected via a questionnaire in November 2021. The study reveals overtourism symptoms in Wroclaw, while their influence on selected city features is not recognized by entrepreneurs as a threat. Negative and positive effects of tourism in Wroclaw are identified on the basis of research that considered (via nonprobability sampling) the opinions of entrepreneurial representatives participating in tourism organization and service from several sectors of the tourism economy. The findings presented here will help mitigate the above issues while neutralizing the threat of overtourism and its negative impacts.